Rapid COVID‐19 antigenic tests: Usefulness of a modified method for diagnosis. Issue 9 (31st May 2021) - Soleimani, Reza; Deckers, Corentin; Huang, Te‐Din; Bogaerts, Pierre; Evrard, Stéphanie; Wallemme, Isaline; Habib, Boutaina; Rouzé, Pauline; Denis, Olivier
Abstract: The current reliable recommended test for coronavirus disease 2019 (COVID‐19) diagnosis is quantitative reverse‐transcription polymerase chain reaction (RT‐qPCR). Rapid antigen test devices could be useful as they are less expensive, faster without the need of specialized laboratories to perform the test. We report the performances of two rapid immunochromatographic antigen testing devices compared with RT‐qPCR for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) detection in nasopharyngeal samples. We carried out a lateral‐flow tests study on 401 nasopharyngeal swab samples from nonduplicated suspected COVID‐19 subjects. An equal volume of universal transport medium tubes‐containing samples (dilution ratio = 1:15) were added to the manufacturer's extraction buffer solution (dilution ratio = 1:2) and analyzed on BioSpeedia COVID19Speed‐Antigen Test and on Abbott Panbio™ COVID‐19 Ag Rapid Test, devices. Qualitative results were compared to those obtained by the RT‐qPCR (Allplex™ SARS‐CoV‐2 Assay Seegene). Based on our data, the overall sensitivity for BioSpeedia and Panbio devices was estimated at 65.5% and 75.0%, respectively. The sensitivity was greater for cycle threshold values less than 25 achieving 90.4 and 96.8 for BioSpeedia and Panbio devices, respectively. A perfect specificity of 100.0% was observed for both devices. Highlights: We evaluated the performances of two rapid COVID‐19 antigen tests, namely BioSpeedia COVID19Speed‐Antigen Test and Abbott Panbio™ COVID‐19 Ag Rapid Test, during the second wave of COVID‐19 pandemic in Belgium. For this purpose, 401 nasopharyngeal swab samples from suspected COVID‐19 subjects were analyzed on both devices with a modified method and the results were compared with those obtained on the routine platform RT‐qPCR (Seegene, Allplex™). Our data showed a high sensitivity (>90.0%) for samples with high viral load (Ct < 30 and particularly Ct < 25). Based on our data, both devices could be reliable and efficient alternative tests during COVID‐19 outbreaks, particularly in a high prevalence population, when there is limited availability of molecular tests to quickly rule in positive patients.